2017
DOI: 10.3390/microorganisms5010008
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Rhodoferax antarcticus ANT.BRT; A Psychrophilic Purple Nonsulfur Bacterium from an Antarctic Microbial Mat

Abstract: Rhodoferax antarcticus is an Antarctic purple nonsulfur bacterium and the only characterized anoxygenic phototroph that grows best below 20 °C. We present here a high-quality draft genome of Rfx. antarcticus strain ANT.BRT, isolated from an Antarctic microbial mat. The circular chromosome (3.8 Mbp) of Rfx. antarcticus has a 59.1% guanine + cytosine (GC) content and contains 4036 open reading frames. In addition, the bacterium contains a sizable plasmid (198.6 kbp, 48.4% GC with 226 open reading frames) that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 61 publications
1
24
1
Order By: Relevance
“…All the members of genus Rhodoferax are motile by polar flagella except for Rhodoferax bucti [1][2][3][4][5][6][7]. This genetic evidence of motility by flagella and type IV pili in Rhodoferax antarcticus was found in previous observations by Baker et al [8], in which the genes coding proteins synthesizing polar flagella, fliEFGHIJKLMNPQR, were well studied.…”
Section: Motilitysupporting
confidence: 63%
See 3 more Smart Citations
“…All the members of genus Rhodoferax are motile by polar flagella except for Rhodoferax bucti [1][2][3][4][5][6][7]. This genetic evidence of motility by flagella and type IV pili in Rhodoferax antarcticus was found in previous observations by Baker et al [8], in which the genes coding proteins synthesizing polar flagella, fliEFGHIJKLMNPQR, were well studied.…”
Section: Motilitysupporting
confidence: 63%
“…Cell growth was investigated in different bacteriological media: R2A agar, tryptic soy agar (TSA; Difco, NJ, USA), Luria-Bertani (LB; Difco, NJ, USA) and nutrient agar (NA; Difco, NJ, USA). The growth temperature range was checked at 4,8,15,20,30,37 and 42 • C. The pH range for growth was determined by measuring the OD values of R2A broth cultures after 3 days. Then, pH was adjusted to 5-10 at intervals of 1 pH unit with appropriate biological buffers [18,19].…”
Section: Morphological Physiological and Chemotaxonomic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the Rhodoferax species are capable of anoxygenic photoorganotrophy, anaerobic-dark fermentation, aerobic respiration and anaerobic growth via sugar fermentation, and the species in this genus are Gram-stain-negative, rod- or slightly curved rod-shaped bacteria containing ubiquinone-8 as the major respiratory quinone, and the G+C content is in the range of 59.5–62.8 mol% [1–7]. The genetic blueprint of a psychrophilic purple non-sulfur bacterium, Rhodoferax antarcticus ANT.BR T , has revealed that it has the photosynthetic machinery to survive under varying environmental conditions [8]. Here, we report on the analysis of the genome of a nonphototrophic strain, Gr-4 T , together with a taxonomic proposal based on its phylogenetic, genomic, physiological and chemotaxonomic characteristics.…”
Section: Introductionmentioning
confidence: 99%